Mesopolysaccharides: the extracellular surface layer of visceral organs - Wagner, Willi Linus; Horstmann, Heinz; Kuner, Thomas; Schwab, Yannick; Konietzke, Philip; Wünnemann, Felix; Wielpütz, Mark Oliver; Kauczor, Hans-Ulrich (PLOS ONE, 2020)
The mesothelium is a dynamic and specialized tissue layer that covers the somatic cavities (pleural, peritoneal, and pericardial) as well as the surface of the visceral organs such as the lung, heart, liver, bowel and tunica vaginalis testis. The potential therapeutic manipulation of visceral organs has been complicated by the carbohydrate surface layer—here, called the mesopolysaccharide (MPS)—that coats the outer layer of the mesothelium. The traditional understanding of MPS structure has relied upon fixation techniques known to degrade carbohydrates. The recent development of carbohydrate-preserving fixation for high resolution imaging techniques has provided an opportunity to re-examine the structure of both the MPS and the visceral mesothelium. In this report, we used high pressure freezing (HPF) as well as serial section transmission electron microscopy to redefine the structure of the MPS expressed on the murine lung, heart and liver surface. Tissue preserved by HPF and examined by transmission electron microscopy demonstrated a pleural MPS layer 13.01±1.1 um deep—a 100-fold increase in depth compared to previously reported data obtained with conventional fixation techniques. At the base of the MPS were microvilli 1.1±0.35 um long and 42±5 nm in diameter. Morphological evidence suggested that the MPS was anchored to the mesothelium by microvilli. In addition, membrane pits 97±17 nm in diameter were observed in the apical mesothelial membrane. The spatial proximity and surface density (29±4.5%) of the pits suggested an active process linked to the structural maintenance of the MPS. The striking magnitude and complex structure of the MPS indicates that it is an important consideration in studies of the visceral mesothelium.